2016
DOI: 10.3389/fpsyg.2015.02002
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a Short Measure of Shared Servant Leadership Impacting Team Performance through Team Behavioral Integration

Abstract: The research reported in this paper was designed to study the influence of shared servant leadership on team performance through the mediating effect of team behavioral integration, while validating a new short measure of shared servant leadership. A round-robin approach was used to collect data in two similar studies. Study 1 included 244 undergraduate students in 61 teams following an intense HRM business simulation of 2 weeks. The following year, study 2 included 288 students in 72 teams involved in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…Teams were exposed either to a leader using inspirational motivation, intellectual stimulation, or a control condition. Our findings reveal important differences between leadership styles in communication and team outcomes (objective task performance and creativity), Sousa and Van Dierendonck (2016), Neil, Wagstaff, Weller, and Lewis (2016), Liu et al (2015), Zhang, Cao, and Tjosvold (2011), and Hoch and Kozlowski (2014). All of these studies concluded that team performance is directly linked to leadership, especially transformational leadership, but none of them evaluated the difference in this performance in projects with distinct management methods, that is, traditional and agile.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Teams were exposed either to a leader using inspirational motivation, intellectual stimulation, or a control condition. Our findings reveal important differences between leadership styles in communication and team outcomes (objective task performance and creativity), Sousa and Van Dierendonck (2016), Neil, Wagstaff, Weller, and Lewis (2016), Liu et al (2015), Zhang, Cao, and Tjosvold (2011), and Hoch and Kozlowski (2014). All of these studies concluded that team performance is directly linked to leadership, especially transformational leadership, but none of them evaluated the difference in this performance in projects with distinct management methods, that is, traditional and agile.…”
Section: Introductionmentioning
confidence: 82%
“…Our findings reveal important differences between leadership styles in communication and team outcomes (objective task performance and creativity) verified that communication and trust are essential for leadership, specifically for the transformational style. Sousa and Van Dierendonck (2016) identified leadership shared by the leader as having a strong influence on team integration, increasing team performance due to the sharing of information. Neil, Wagstaff, Weller, and Lewis (2016) studied the transformational leadership style, indicating that the way the team works to achieve important goals and the use of the emotional intelligence of team members have a direct impact on performance.…”
Section: Team Performancementioning
confidence: 99%
“…Integration is higher if leaders exhibit an empowering leadership style in which they “communicate confidence that the team can accomplish ambitious collective goals,” “model collaborative behaviors and encourage followers to be more collectively committed to group objectives,” and “promote cooperative behavior among team members through verbal suasion and persistent appeals for collaboration” (Carmeli et al, , p. 401). Leadership styles related to empowering leadership, such as servant leadership (Sousa & Van Dierendonck, ) and transformational leadership (Friedman et al, ), also positively influence group behavioral integration. A common characteristic underlying these styles is humility, which is “a self‐view of accepting that something is greater than the self, and manifests in self‐awareness, openness to feedback, appreciation of others, low self‐focus, and self‐transcendent pursuit”; humility is positively related to empowering leadership, which, in turn, positively predicts behavioral integration (Ou et al, ).…”
Section: Theory Developmentmentioning
confidence: 99%
“…(3) The third stage, which we will call model development, where we can find many works which represent sophisticated models which can be used to analyze the background of servant leadership, its relationship with performance and even the analysis of mediation and/or moderation factors. In this stage, the works of Liden et al (2014), Flynn et al (2016), Sousa and van Dierendonck (2016), Sendjaya et al (2019) are particularly noteworthy.…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Third Sector entities are not unaware of these changes, so it is necessary to analyze whether this new approach can be used by Third Sector entities to improve their performance. Although the relationship between servant leadership and performance has been studied in other sectors (see Liden et al, 2008;Overstreet et al, 2014;Huang et al, 2016;Sousa and van Dierendonck, 2016;Hoch et al, 2018;Lee et al, 2019) it has not been addressed in Third Sector entities. In this sense, this work attempts to respond to the call from authors such as Ronquillo (2011) and Allen et al (2018) to analyze servant leadership in Third Sector entities, raising the following research question: Does servant leadership influence the performance of Third Sector entities?…”
Section: Introductionmentioning
confidence: 99%